Analysis of Efficiency, Effectiveness of Land and Building Tax Revenue (PBB) and Its Contribution to Regional Original Revenue (PAD) of Mataram City in 2018-2022 - Nisak, Attin Zaetun; Masrun; Astuti, Endang (West Science Business and Management, 2024)
This research aims to determine and analyze the level of efficiency and effectiveness of Mataram City's land and building tax (PBB) revenue, as well as analyzing the contribution of land and building tax (PBB) to Mataram City's local revenue (PAD) in 2018-2022. The type of research used in this research is quantitative descriptive. The results of this research show that the efficiency of Mataram City's land and building tax (PBB) revenue shows a large efficiency ratio in the last 5 years, namely 2018-2022, which has an average ratio of 1.18% with very efficient criteria. The effectiveness of Mataram City's land and building tax (PBB) revenue shows that in the last 5 years, namely 2018-2022, the average effectiveness ratio of land and building tax (PBB) was 102.39% with very effective criteria. The contribution of land and building taxes (PBB) to Mataram City's original regional income (PAD) in the last 5 years 2018-2022 has an average ratio of 6.46% with the criteria of very little contribution.